2001
DOI: 10.2307/4003168
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and Water Yield Dynamics in an Edwards Plateau Watershed

Abstract: Woody cover, when expressed at the scale of the 207 km 2 Cusenbary Draw basin, remained unchanged (~23%) from 1955 to 1990. When expressed at the scale of range sites, woody cover declined on sites with relatively high production potential and increased on sites with relatively low production potential. Change in woody cover distribution at sub-range site scales, increased low and high woody covers and decreased intermediate woody cover, would be expected to lead to increased water yield at the basin scale bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…The degree to which woody and encroached communities increase water erosion (either through physical effects or by reducing infiltration) is poorly understood (Eldridge et al, 2003). Hydrological models have been used to study how the amount of rainfall reaching the ground, and hence the risk of erosion, varies according to changing cover of woody plant canopies (Wu et al, 2001). As woody vegetation tends to intercept more rainfall than understory vegetation (Thurow, 1991;Wu et al, 2001), it could be argued that woody vegetation reduces the risk of erosion to a greater degree.…”
Section: The Effects At Plot Scalementioning
confidence: 99%
“…The degree to which woody and encroached communities increase water erosion (either through physical effects or by reducing infiltration) is poorly understood (Eldridge et al, 2003). Hydrological models have been used to study how the amount of rainfall reaching the ground, and hence the risk of erosion, varies according to changing cover of woody plant canopies (Wu et al, 2001). As woody vegetation tends to intercept more rainfall than understory vegetation (Thurow, 1991;Wu et al, 2001), it could be argued that woody vegetation reduces the risk of erosion to a greater degree.…”
Section: The Effects At Plot Scalementioning
confidence: 99%
“…In the 1960s and 1970s, the potential for such a strategy was extensively investigated in the southwestern United States; anecdotal observations and estimates of ET savings associated with shifts in cover type from trees/shrubs to grasses led to the conclusion that there was significant potential for an increase in localized water yield (summarized by Hibbert 1983). In addition, modeling studies have indicated that the effects of shrub encroachment on water yield may be important on rangelands where drainage is rapid and deep (Wu et al 2001;Afinowicz et al 2005).…”
Section: Emerging Issues For Ecohydrology Research In Rangelandsmentioning
confidence: 99%
“…Concern has been raised that juniper may contribute to aquifer drawdown due to high year-round transpiration rates. Woody plant control may provide potential water savings to the region (Dugas and Mayeux 1991;Wu et al 2001;Wilcox 2002;Wilcox et al 2005). For woody plant management to successfully enhance groundwater recharge, the vegetation remaining after land clearing must use significantly less water than pretreatment vegetation.…”
Section: Introductionmentioning
confidence: 99%